Frequency of IgA and IgM anti Chlamydia Trachomatis Antibodies in Pregnant Women Coming from a Prenatal Consult in Cumana, State of Sucre, Venezuela, March-June of 2006 - Henry De Freitas F.; Luisa Caña G.; Lilian Caña G.; Maribel Rosales (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
In order to establish the frequency of IgA and IgM anti-C. Trachomatis antibodies in expectant women, a study was made of 84 women between the ages of 14 and 43, who attended prenatal consults in the Autonomous Service at the University Hospital "Antonio Patricio of Alcalá," Cumaná, State of Sucre, during the March-June period, 2006. 84 serum samples were obtained to determine IgA and IgM anti-C. trachomatis antibodies using the immunoabsorption method connected to ELISA enzymes (Diagnostic Automation INC). Of the total samples studied, 16 (19.05%) and 55 (65.48%) resulted positive for the IgA and IgM anti-C. trachomatis antibodies, respectively. No association was found between the presence of these antibodies and the age of the patients, although the greater number of positive patients was in the 14 to 23 year age interval. Likewise, no statistically significant values were found between the association of clinical genital manifestations and the presence of IgA and IgM anti C- trachomatis antibodies; therefore, it was shown that Chlamydia trachomatis is presented asymptomatically in most cases. Conclusions were that genital infection by Chlamydia trachomatis in pregnant women is extremely frequent, especially for ages between 24 and 33 years, and it occurs habitually in an asymptomatic form with the serious repercussions that this produces on the patient, the fetus and the partner.